Neuromuscular and lower limb biomechanical differences exist between male and female elite adolescent soccer players during an unanticipated run and crosscut maneuver - Landry, S. C.; McKean, K. A.; Hubley-Kozey, C. L.; Stanish, W. D.; Deluzio, K. J. (The American Journal of Sports Medicine, 2007)
Noncontact anterior cruciate ligament injuries often occur during sports such as soccer and basketball in which cutting or landing maneuvers are frequently performed. These injuries are more common in female athletes, and identifying biomechanical or neuromuscular risk factors related to gender may help with the development of preventive training programs aimed at reducing anterior cruciate ligament injury.